An Assessment of Pediatric Dental Caries and Family Quality of Life in an Informal Amazonian Community - Marc Horton; Sahar Zolfaghari; Eduardo Bernabé; Leann Andrews; Jorge Alarcón; Mauro Echevarría; Joseph Zunt; Ana Lucia Seminario (Ubiquity Press, 2021)
Background: Oral diseases are among the most prevalent non-communicable diseases worldwide, disproportionally affecting vulnerable populations. The Community of Claverito is one of many informal urban floating communities located on the Amazon River in Peru. Objectives: To assess child and caregiver dental health status (DHS) and to measure the associations between child DHS and child and family quality of life in the informal Community of Claverito. Methods: DHS, as measured by decayed and filled teeth (DFT/dft), was recorded for 66 children and 35 caregivers using the WHO Oral Assessment form. Oral health-related quality of life was measured using the Parental-Caregiver Perceptions Questionnaire (P-CPQ). The family impact of child oral disorders was measured using the Family Impact Scale (FIS). Descriptive statistics, correlations, and regression analyses were used to evaluate the associations between DFT/dft, P-CPQ, and FIS scores (p < 0.05). Findings: The majority of children assessed were female (52%) with a mean age of 9.4 years (SD ± 4.4). The prevalence of untreated child dental caries was 97%. The child and caregiver's mean DFT/dft scores were 6.8 (SD ± 4.5) and 8.7 (SD ± 13.3), respectively. Mean total P-CPQ and total FIS scores were 33.4 and 12.5, respectively. A significant positive association was observed between child DFT/dft scores and total FIS scores (p < 0.01). Significant associations were also observed between child DFT/dft scores and caregiver age (p < 0.01) and child DFT/dft scores and caregiver DFT scores (p < 0.01). Conclusions: Children and their caregivers living in the Community of Claverito exhibited high levels of dental caries. Children's untreated dental caries were associated with both family's quality of life and caregivers' untreated dental caries. Further research is needed on how improving availability and access to oral health services have the potential to benefit the health of residents of informal communities like the one of Claverito.